The Correlation between Knowledge of Microbiology and Biology Education Students Hygiene Attitude - Indriani, Bayuni; Muzajjanah, M; Wulaningsih, Ratna Dewi (Biosfer: Jurnal Pendidikan Biologi, 2014)
Diseases can be caused by pathogenic microorganism that appears due to unhygienic attitude. Hygiene attitude have to be integral part of human life. The increasing of hygiene attitude can be reached by continuous education. The right knowledge that can forms and increases hygiene attitude is microbiology. The aim of this research is to know the correlation between knowledge of microbiology and Biology Education Students’ Hygiene Attitude. It was conducted at Jurusan Biologi FMIPA UNJ on April-May 2012. The method of this research that used is descriptive method with survey technique. The samples of this research are 50 Biology education studentsof class 2008. Samples were taken by simple random sampling technique. Prerequsite tests that used were normality test of Kolmogorov-Smirnov by SPSS 16.0 and Test of Homogenity of Variances (levene statistic) by SPSS 16.0. Statistic test which used was nonparametric technique by correlation test of Spearman Rank by SPSS 16.0. Result of the research shows that there is correlation between knowledge of microbiology and Biology Education Students’ Hygiene Attitude.